Fine Structures of $1s^2np$ and $1s^2nd$ States for $Zn^{27+}$ Ion (Journal of Atomic and Molecular Sciences, 2012)
The non-relativistic energies and wavefunctions of $1s^2np$ and $1s^2nd$ states for $Zn^{27+}$ ion are obtained by using the full-core plus correlation method. The expectation values of the spin-orbit and spin-other-orbit interaction operators in these states are calculated. By introducing the effective nuclear charge, the higher-order relativistic contribution and QED correction to the fine structure splittings are estimated.